A review of the subfamily Centrocneminae (Hemiptera: Heteroptera: Reduviidae) from Sumatra - Li, Hu; Yan, Keyu; Constant, Jerome; Cai, Wanzhi (Zootaxa, 2009)
Two genera and two species, Neocentrocnemis signoreti (Stål, 1863) and Centrocnemoides sumatrana Miller, 1956, in the subfamily Centrocneminae from Sumatra, are recognized and redescribed. The male genitalia of the two species are described and illustrated for the first time, except for the paramere of N. signoreti.